2018
DOI: 10.1038/s41598-018-26603-1
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial protease HtrA2 restricts the NLRP3 and AIM2 inflammasomes

Abstract: Activation of the inflammasome pathway is crucial for effective intracellular host defense. The mitochondrial network plays an important role in inflammasome regulation but the mechanisms linking mitochondrial homeostasis to attenuation of inflammasome activation are not fully understood. Here, we report that the Parkinson’s disease-associated mitochondrial serine protease HtrA2 restricts the activation of ASC-dependent NLRP3 and AIM2 inflammasomes, in a protease activity-dependent manner. Consistently, disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 73 publications
1
16
0
Order By: Relevance
“…Rodrigue et al reported that ROS levels were similar in macrophages of HtrA2 mnd2(-/-) mice compared to WT [33], which is in agreement with our results. Conversely, three independent studies showed significantly elevated production of ROS in HtrA2/Omi KO mouse embryonic fibroblasts (MEFs) [30,74,75].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Rodrigue et al reported that ROS levels were similar in macrophages of HtrA2 mnd2(-/-) mice compared to WT [33], which is in agreement with our results. Conversely, three independent studies showed significantly elevated production of ROS in HtrA2/Omi KO mouse embryonic fibroblasts (MEFs) [30,74,75].…”
Section: Discussionsupporting
confidence: 93%
“…However, the upregulation of UPR mt -related genes were not observed in HtrA2 mnd2(-/-) brain [30]. ROS levels were also found to be similar in macrophages of HtrA2 mnd2(-/-) mice compared to wild type (WT) [33]. Taken together, these facts raises the question of whether the cytoprotective effect of HtrA2/Omi might be achieved in a manner of mitonuclear signaling.…”
Section: Introductionmentioning
confidence: 87%
“…Very recently, Rodrigue‐Gervais et al (2018) showed that HtrA2 can inhibit ASC‐dependent activation of the NLRP3 and AIM2 inflammasomes in BMDMs. The HtrA2 protease can regulate autophagy and the magnitude and duration of the inflammasome pathway by preventing long‐term accumulation of ASC …”
Section: Nlrp3 Inflammasome‐mediated Inflammatory Pathways In Pdmentioning
confidence: 99%
“…Initially, the roles of HtrA2/Omi in apoptosis, mitochondrial protein folding quality control, and cell survival were investigated [9]. A recent study reported that HtrA2/Omi regulates autophagy and inflammasome signaling by preventing prolonged accumulation of the inflammasome adaptor ASC [44]. In addition, Michell et al found that expression of the pro-apoptotic protein Bcl-2 in the liver protected against CCl 4 induced-mitochondrial dysfunction and -oxidative stress in hepatocytes [8].…”
Section: Discussionmentioning
confidence: 99%